Regulatory mechanisms of the gut microbiota-short chain fatty acids signaling axis in slow transit constipation and progress in multi-target interventions - Liu, Shi Hong; Yang, Xue Fang; Liang, Lei; Song, Bin Bin; Song, Xue Mei; Yang, Yong Jun; Alhoot, Mohammed Abdelfatah (Frontiers in Microbiology, 2025)
Slow-transit constipation (STC) is an increasingly prevalent disorder that imposes a substantial health and economic burden. Mounting evidence highlights the “gut microbiota–short-chain fatty acid (SCFA)–motility” axis as a central pathophysiological link between dysbiosis and impaired colonic transit. This review synthesizes current knowledge of how SCFAs, especially acetate, propionate and butyrate, shape motility through serotonergic signaling, enteric nervous system modulation, epithelial barrier integrity and immune regulation. Particular attention is devoted to the biased-signaling properties of the SCFA receptors FFAR2 and FFAR3 (free fatty acid receptors 2 and 3, respectively), including emerging data on their heterodimerization. The article then appraises recent randomized controlled trials and meta-analyses of multi-target interventions (dietary fibers, synbiotics, postbiotics, fecal microbiota transplantation, phytochemicals, and small-molecule FFAR agonists) highlighting their efficacy, safety, and translational hurdles. Finally, the authors propose a precision-medicine framework that integrates multi-omics microbiome profiling, metabolomics, and host genetics to enable phenotype-stratified therapy. Key research gaps include limited long-term safety data, heterogeneous human cohorts and the need for large multicenter trials and machine-learning-guided responder prediction. Collectively, the review provides a roadmap for shifting STC management from symptom control to mechanism-based, personalized care.